2016
DOI: 10.4314/tjpr.v15i7.28
|View full text |Cite
|
Sign up to set email alerts
|

Moderating effects of contextual factors on relationship between pharmaceutical marketing strategies and physician prescription decision: A review

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Some factors include marketing efforts, patients’ drug requests and patients’ expectations are likely responsible for inappropriate prescriptions 9-16. Furthermore, contextual factors like drug attributes, habit persistence, and cost/benefits of the drug are found to exist during the time of the prescription 17-20. Pharmacist expertise and collaboration factors may also offer many opportunities for modification prescribing decisions 21-25…”
Section: Introductionmentioning
confidence: 99%
“…Some factors include marketing efforts, patients’ drug requests and patients’ expectations are likely responsible for inappropriate prescriptions 9-16. Furthermore, contextual factors like drug attributes, habit persistence, and cost/benefits of the drug are found to exist during the time of the prescription 17-20. Pharmacist expertise and collaboration factors may also offer many opportunities for modification prescribing decisions 21-25…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the relationship between physicians and pharmaceutical companies as regards decision‐making in drug prescription has instigated controversy . This possible conflict of interest between physicians and pharmaceutical companies poses a significant concern, mainly because there is no consensus among researchers about the influence of marketing efforts on the prescription decisions of physicians . The relationship between different marketing actions and evidence of how they influence drug prescribing remains inconclusive .…”
Section: Introductionmentioning
confidence: 99%
“…[4,9] This possible conflict of interest between physicians and pharmaceutical companies poses a significant concern, mainly because there is no consensus among researchers about the influence of marketing efforts on the prescription decisions of physicians. [10] The relationship between different marketing actions and evidence of how they influence drug prescribing remains inconclusive. [11] Some researchers found that marketing efforts positively affect the prescribing decisions of physicians.…”
Section: Introductionmentioning
confidence: 99%
“…Another study reported the spending on drug promotion to be $28 billion in the United States, $26 billion in Japan and $20 billion in UK, France, Germany, Spain and Italy, estimating the overall share of promotional activities to reach $90 billion by 2012 . Other study estimated the overall spending of pharmaceutical industry on marketing to range from 20 to 40% of its revenue . Almost all these studies highlighted physicians as the prime target of promotional activities, and medical representatives (MRs) as the prime tool playing a crucial role in the promotional activities that target physicians.…”
Section: Introductionmentioning
confidence: 99%